Numerical Modeling Chemical Vapor Infiltration of SiC Composites - Yaochan Zhu; Eckart Schnack (Journal of Chemistry)
The multiphase field model for chemical vapor infiltration (CVI) of SiC/SiC composites is developed in this study, thereby to reproduce the microstructure evolution during CVI process and to achieve better understanding of the effect of process parameters (e.g., temperature, pressure, etc.) on the final product. In order to incorporate the thermodynamics of methyltrichlorosilane (MTS) pyrolysis into phase field model framework, the reduced chemical reaction mechanism is adopted. The model consists of a set of nonlinear partial differential equations by coupling Ginzburg-Landau type phase field equations with mass balance equations (e.g., convection-diffusion equation) and the modified Navier-Stokes equations which accounts for the fluid motion. The microstructure of preferential codeposition of Si, SiC under high ratio of H2 to MTS is simulated and the potential risk of blockage of the premature pores during isothermal CVI process is predicted. The competitive growth mechanism of SiC grains is discussed and the formation process of potential premature pore blockage is reproduced.